Differences in shooting kinematics between experienced and non-experienced wheelchair basketball athletes - Yang, Y.; Johnson, Q. R.; Scott, A. A.; Nquyen, M. N. Q.; Cabarkapa, D.; Fry, A. C. (International Journal of Exercise Science Conference Proceedings, 2025)
Wheelchair basketball (WCB) is one of the most popular paralympic sports. While shooting efficiency is one of the key performance parameters related to on-court success, limited research to date has investigated shooting mechanics within this specific cohort of athletes. PURPOSE: The present study aimed to compare the shooting kinematics between experienced and non-experienced WCB athletes. METHODS: Eight male athletes (x¯±SD; age=31.9±8.9 years; sitting height=71.9±6.7 cm; body mass=78.9±15.1 kg) who were members of a national-level WCB team performed 10 two-point shots (5.10 m) while facing directly to the basket. A video camera recording at 60 fps as positioned 10 m away, perpendicular to the subject`s plane of motion, to record the shooting motion from a sagittal point of view. A video analysis software was used to analyze two-dimensional kinematic parameters: elbow angle (EA), relative initial ball height (BH) and release height (RH) adjusted by the athlete`s sitting height, release time, and release angle. Subjects were separated into experienced players (EG, n=4; >5 years of playing experience) and non-experienced players (NG, n = 4; novice athletes). Due to data violating the assumption of normality, median and interquartile ranges were reported. Shooting kinematic differences between groups were examined using Mann-Whitney U-tests (p